Performance methods of Lawk and Hayranok: A comparative study - Zana Jabali Mamand; Nasser Hashim Badan; Nareman Abdullah Kareem (QALAAI ZANIST JOURNAL, 2024)
This research talks about one of the kurdish folklore song forms, called Lawk. Lawk is a kind of free-rhythmic Kurdish folklore song that the length of its voices depends on the need of the words and the wish of the singer. This research shows the definition and dialect of Lawk and describes the geographical location of it and how the performance of this type of folklore song is performed. it explains the types of Lawk as a content, scale and intervals. This research shows the specialties of Lawk and distinguishes it from other Kurdish song forms. Lawk is a great national wealth that historically tells many stories and historical stories to us and a type of song that is special to the Kurdish nation.